Donor–acceptor interactions in tri(phosphonio)methanide dications [(Ph3P)2CP(X)Ph2]2+ (X = H, Me, CN, NCS, OH, Cl, OTf, F). Issue 44 (1st November 2017) - Yogendra, S.; Hennersdorf, F.; Bauzá, A.; Frontera, A.; Fischer, R.; Weigand, J. J.
Abstract : The impact of the strongly electron donating carbodiphosphorane moiety in the series of tri(phosphonio)methanide dications as triflate salts [(Ph3 P)2 CP(X)Ph2 ][OTf]2 (X = H, Me, CN, NCS, OH, Cl, OTf, F) deriving from [(Ph3 P)2 CPPh2 ][OTf] (19 [OTf]) is presented. Abstract : The impact of the strongly electron donating carbodiphosphorane moiety in the series of tri(phosphonio)methanide dications as triflate salts [(Ph3 P)2 CP(X)Ph2 ][OTf]2 (X = H, Me, CN, NCS, OH, Cl, OTf, F) deriving from [(Ph3 P)2 CPPh2 ][OTf] (19 [OTf]) is presented. The influence of the introduced substituents X on the electronic structures of these dications is investigated by means of detailed NBO analysis, NMR spectroscopy and X-ray analysis.